COVID-19 and Its Influence on the Mental Well-being of People with Co-Morbidities: A Qualitative Study at a Public Healthcare Clinic - Sunil Neerputh; Raisuyah Bhagwan; Firoza Haffeejee (African Journal of Inter-Multidisciplinary Studies, 2025)
People with co-morbidities are at greater risk of disease severity from COVID-19 due to their compromised immunity. COVID-19 and the mitigation measures implemented in South Africa negatively influenced the mental health of people with co-morbidities. The study explored how the mental health of patients with co-morbidities was affected during the pandemic and post the initial waves of COVID-19. Drawing on patients at a public clinic in the province of KwaZulu-Natal and through a qualitative research approach, semi-structured interviews, were held to understand how the mental health well-being of patients was affected. Two groups of 26 participants were recruited using non-probability sampling methods. Sample one comprised participants with co-morbidities but not infected by the virus. Sample two comprised participants with co-morbidities who were infected by SARS-CoV-2 and after three months. The data was analysed using thematic analysis. Six themes were derived from the data and focussed on aspects related to fear and anxiety, loneliness, trauma linked to COVID-19, stress, somatisation, and spirituality. Many people experienced these debilitating emotions and suffered enormous mental health sequelae due to the pandemic, much of which was exacerbated by their co-morbidities.